Quality Service Delivery Between Service Failure and Service Recovery in Hospitality Industry: A Place for Enjoyment - Houshyar Abdulrahman Saleh; Vinnaras Nithyanantham (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
Having good customer satisfaction by providing excellent quality services are important in running a successful hospitality business. Every establishment needs to deliver quality service and quality products, which are critical, factors for the success of any business. Also, Managers need to understand how to encourage their staff to implement quality measures to assure service guarantee and retain customer relationships to implicate the re-visit and deliver the positive word of mouth. This study aims to explore the effect of delivery of quality service and service recovery on tourism satisfaction including the success of the business. The exploration involves how to recover a service failure and how to improve employee performance through examination of the gap between management and customer’s expectation. This study has revealed that quality service and customer satisfaction are critical factors for the success of hospitality and tourism business. In this research as a part of the qualitative research, the focus group interviewing is used to obtain adequate information from the participants to understand their perception to assess the delivery of the quality service and the techniques of recovery approach after showing the service failure.